Exploring tetrazole chemistry: synthetic techniques, structure–activity relationship, and pharmacological insights in antimicrobial and anticancer therapy - Maji, Lalmohan; Teli, Ghanshyam; Pal, Rohit; Maheshwari, Neelesh; Soni, Praveen Kumar; Matada, Gurubasavaraja Swamy Purawarga; Rathore, Mahendra Singh; Saravanan, Venkatesan; Muthukumaradoss, Kathiravan (Frontiers in Chemistry, 2025)
Tetrazoles are nitrogen-rich heterocycles that have attracted interest because of their numerous applications in pharmaceutical and medicinal chemistry. Four nitrogen atoms and one carbon atom make up these five-membered rings, which have special physicochemical and electrical characteristics, including acidity, resonance stabilization, and aromaticity. This article highlights the structure, spectroscopic characteristics, and physical and chemical characteristics of tetrazoles. It also describes how overlapping mechanisms, such as DNA replication inhibition, protein synthesis disruption, and oxidative stress induction, as well as similar therapeutic targets, enable inhibitors to serve as both antibacterial and anticancer agents. Tetrazole moieties have been fused with a range of pharmacophores, such as indoles, pyrazoles, quinolines, and pyrimidines, yielding fused derivatives that display substantial inhibitory activity against bacterial, fungal, and cancer cell lines, with certain compounds exhibiting efficacy comparable to or exceeding that of established therapeutic agents. The rational design of more efficacious tetrazole-based therapies is facilitated by structure–activity relationship analysis, which further highlights significant functional groups and scaffolds that contribute to increasing activity. We investigate the relationship between microbial inhibition and anticancer efficacy, opening up new avenues for the creation of multifunctional therapeutic agents. We hope that this study will offer significant guidance and serve as a valued resource for medicinal and organic researchers working on drug development and discovery in multifunctional therapeutics. The review involves a thorough investigation of tetrazole in recent years.